2010
DOI: 10.1002/adsc.201000005
|View full text |Cite
|
Sign up to set email alerts
|

Base‐ and Copper‐Catalyzed Intramolecular Cyclization for the Direct Synthesis of Dihydrofurans

Abstract: A simple and convenient synthetic approach to dihydrofurans has been developed from the cyclization of 2-propynyl-1,3-dicarbonyl compounds catalyzed by potassium tert-butoxide, copper(II) trifluoromethanesulfonate and triphenylphosphine using methanol/dichloromethane as the solvent under very mild conditions. Moreover, dihydrofurans could be easily transformed into the corresponding furans in the presence of trifluoroacetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Furthermore, α-alkylation of 9a – b provided 10a – c in good yields (88%–92%) for generating the skeleton of 2-arylfuran with a 3-electronwithdrawing group (see eq 2, Scheme ). With 10a – c in hand, Bi­(OTf) 3 -mediated cycloisomerization of γ-alkynones 10a – c with the α-ester and benzoyl groups in the presence of molecular sieve in MeNO 2 at rt for 3 h afforded furans 11a – c in 60–81% . In particular, 12 was isolated in a 25% yield via an intramolecular aldolization of the resulting benzoyl δ-diketone of 10c .…”
mentioning
confidence: 99%
“…Furthermore, α-alkylation of 9a – b provided 10a – c in good yields (88%–92%) for generating the skeleton of 2-arylfuran with a 3-electronwithdrawing group (see eq 2, Scheme ). With 10a – c in hand, Bi­(OTf) 3 -mediated cycloisomerization of γ-alkynones 10a – c with the α-ester and benzoyl groups in the presence of molecular sieve in MeNO 2 at rt for 3 h afforded furans 11a – c in 60–81% . In particular, 12 was isolated in a 25% yield via an intramolecular aldolization of the resulting benzoyl δ-diketone of 10c .…”
mentioning
confidence: 99%
“…They proposed the mechanism for this cyclization as shown in Scheme 30. [54] First, enolate 153 was formed from 2-propynyl-1,3-dicartbonyl compounds 151 catalyzed by potassium tert-butoxide. Subsequently, the enolate oxygen anion attacked the carbon-carbon triple bond which was activated by [Cu] 2 + to generate a vinyl-copper adduct 155.…”
Section: Copper-catalyzed Cyclizations Of 4-acetylenic Ketonesmentioning
confidence: 99%
“…We chose propargylated β-ketoester 1a and amine 1b as model substrates. In order to avoid the competitive reaction of oxacyclization 11 , excess amount of amine was used at first. As shown in Table 1, screen of Lewis acid and solvents demonstrated that La(OTf) 3 and PhCF 3 are most effective as catalyst and solvent respectively (entries 1-9).…”
Section: Scheme 1 Design Of α-Aryl Tetrasubstituted and Fully Substimentioning
confidence: 99%